BIOMEDICAL IMAGE SEARCH AND RETRIEVAL ALGORITHMS - Berezsky, O.; Melnyk, G.; Batko, Yu. (International Journal of Computing, 2014)
In this paper algorithm for search the tumour cells images in a database is developed. This algorithm based on shape and colour image features.